The Influence of ROE EPS DER Current Ratio and Claim Expense Risk on Share Prices with Premium Growth - Gregorius, Marco; Januardo Halim, Nicholas; Verina, Verina (PT. Publikasiku Academic Solution, 2024)
This research aims to determine the effect of profitability (ROE and EPS), debt to equity ratio, current ratio, and claims expense risk on share prices with premium growth. The data used was obtained from the annual financial reports of insurance companies listed on the Indonesia Stock Exchange (BEI) for the period 2020-2022. This research used purposive sampling to collect samples and the analysis techniques used were the normality test, multicollinearity test, heteroscedasticity test, autocollinearity test, t statistical test and MRA test (pure moderation). The total sample in the research was 53 companies. The results of this research prove that ROE DER, current ratio, and claim expense risk don’t have any influence on share prices. EPS has a positive influence on share prices and premium growth can not moderate ROE, CR, EPS and claim expense risk variable and share prices.